Analisis Stigma Negatif Terhadap Mantan Narapidana sebagai Faktor Penghambat Reintegrasi Sosial - Salfa Salsabila Arifah; Dona Raisa Monica; Firganefi Firganefi; Heni Siswanto; Refi Meidiantama (Jurnal Ilmu Sosial dan Humaniora, 2026)
The paradigm shift in Indonesia's criminal justice system, enacted by Law Number 22 of 2022 concerning Corrections, emphasizes restoring relationships between inmates and the community through social reintegration schemes. However, the effectiveness of this reintegration often faces challenges from local sociological responses. This article aims to analyze the implementation of social reintegration at the Class IIA Bandar Lampung Narcotics Correctional Institution and to examine the latent sociological-juridical barriers that trigger recidivism. Using an empirical juridical approach with analytical-descriptive specifications, data were collected through in-depth interviews with the Bandar Lampung Narcotics Correctional Institution authorities and the Lampung Regional Office of the Ministry of Law and Human Rights. The analytical tool used is Soerjono Soekanto's Law Enforcement Theory. The results show that although the procedural administrative process of reintegration is carried out according to regulations, the program's substantive success is significantly reduced. The largest latent barriers stem from societal factors and legal culture, including persistent negative stigmatization and a strong collective retributive paradigm. The implication is that social and economic exclusion forces former inmates back into the criminal cycle (recidivism). This study recommends the need for a cross-sectoral social safety net policy involving the local government and the private sector to break the chain of recidivism in Bandar Lampung City.